General Processing Approach for Bistatic SAR Systems: Description and Performance Analysis - Rodriguez-Cassola, Marc; Prats, Pau; López-Dekker, Paco; Krieger, Gerhard; Moreira, Alberto (European Conference on Synthetic Aperture Radar (EUSAR), 2010)
For its intrinsic properties, bistatic SAR processing cannot be approached in the same manner monostatic SAR process- ing is approached. In general, a bistatic SAR processor is more than a powerful focussing algorithm. Because of the lack of precise time (range) and phase (Doppler) references in non-cooperative (and even cooperative) bistatic systems, a prior software synchronisation step is used to correct the residual errors caused by the use of different clocks. Moreover, depending on the bistatic conﬁguration, different kinds of SAR focussing algorithms can be used. Azimuth-invariant conﬁgurations may beneﬁt from the convolution property of the Fourier transform, whereas more general conﬁgurations are better suited for efﬁcient time-domain techniques. A discussion on the performance of three Fourier-domain focussing algorithms, range-Doppler, chirp scaling, and range migration, is included in the paper.
DLR Import::2019-04-03